ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENGGAJIAN KARYAWAN LEMBAGA PERKREDITAN DESA DENGAN METODE PROTOTYPE - Sekartini, Made; Wijaya, I Nyoman Yudi Anggara; Kusuma, Ni Putu Noviyanti (Politeknik Bisnis Indonesia, 2024)
The financial department of the Tanjung Bungkak Traditional Village Credit Institution (LPD) has problems in the employee payroll process. The problem faced by the finance department is that employee payroll is still using Microsoft Excel, where employee salary calculations are still using Excel formulas and the data is not stored in a database so that searching for employee salary data takes a relatively long time. Payslip recording is still retyped using Microsoft Word so that when printing a payslip you are required to open the payroll report that has been created in Microsoft Excel. This is less effective and efficient, because errors can occur in making employee pay slips and result in frequent delays in salary reporting. This research aims to carry out Analysis and Design of a Payroll Cycle Accounting Information System in order to make it easier to computerize the payroll of Tanjung Bungkak Traditional Village LPD employees. The method used is the Prototype Model. The results of the system design that has been created produce a structured and systematic system to increase productivity and reduce errors in the application of appropriate information technology in business operations and can provide the information needed by the parties involved in the Tanjung Bungkak Traditional Village LPD. The interview results show the analysis and design of a payroll information system that has been created according to the needs of each section.